Sustainable dimension adaptation measure in green township assessment criteria - Yaman, Rostam; Thadaniti, Suwattana; Ahmad, Noraini; Muhamad Halil, Faridah; Nasir, N (IOP Publishing, 2018)
Urbanized areas are typically the most significant sources of environmental degradation, thus, an urban assessment criteria tools aiming at equally adapted sustainability dimensions need to be firmly embedded in benchmarking planning and design framework and upon occupancy. The need for integral systematic rating is recognized in order to evaluate the performance of sustainable neighborhood and to promote sustainable urban development. In this study, Green Building Index Township Assessment Criteria (GBI-TAC) will be measure on holistic sustainable dimension pillar (SDP) adaptation in order to assess and redefine the current sustainability assessment criteria for future sustainable neighborhood development (SND). The objective of the research is to find-out whether the current GBI-TAC and its variables fulfilled the holistic SDP adaptations towards sustainable neighborhood development in Malaysia. The stakeholderinclusion approached is used in this research in order to gather professional’s stakeholders’ opinions regarding the SDP adaptations for sustainable neighborhood development. The data were analysed using IBM SPSS AMOS22 Structural Equation Modelling. The findings suggested an adaptation gap of SDP in current GBI-TAC even though all core-criteria supported SDP adaptation, hence lead to further review and refinement for future Neighborhood Assessment Criteria in Malaysia.